No Detention Policy – Why Do We Need It? - SANGAHI, SANDHYA (THE PRIMARY TEACHER, 2015)
Falling levels of achievement amongst children at the early stages of education has been bothering the planners and administrators of the education over a period of time. Having achieved universalisation of elementary education to a large extent, the quality of learning by children has been an issue which actually questions the achievement of universalisation of elementary education in a real sense. The reports of large scale achievement surveys, ASER, 2012 and NCERT achievement survey hints at the low levels of achievement amongst children of primary lasses. Often it is cited that children of class V are not able to read the text meant for class II level children. Such findings and revelations add to the worries of the education system and a whisper begins to spread ‘where all the government money is going’ Recently while exploring the factors which might be causing low level of learning by children, many stakeholders in education pointed towards the ‘No Detention Policy’ (NDP) as a major reason for persistent bad quality of learning resulting in poor learning outcomes. The same voice came from so many quarters that a CABE Subcommittee was set up for Assessment and Implementation of Continuous and Comprehensive Evaluation in the context of the No Detention Policy in the RTE Act, 2009. This sub-committee was chaired by Smt. Geeta Bhukkal, Former Minister of Education, Govt. of Haryana. The major recommendation (not unanimous) of the sub-committee is to do away with the provisions of No Detention up to class VIII. Encouraged by this recommendation many groups including media got involved in heating up the discussion on the Non Detention Policy under the RTE Act. Many state governments started writing to the MHRD for an amendment in the RTE Act to detain children post lass III or V.